Mavis Barnes (front) and Claudette McPherson (back) operating Rumoldi seaming machine (1975)
This is a black and white photograph of 4 persons seated doing their own thing.
Daily News collection, no restriction.
Keywords: Industries- Garment Manufacturing; Photograph